2014
DOI: 10.15171/ijhpm.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

The quality assessment of family physician service in rural regions, Northeast of Iran in 2012

Abstract: There was a gap between the ideal situation and the current situation of family physician quality of services. Our suggestion is maintaining a strong focus on patients, creating a medical practice that would exceed patients' expectations, providing high-quality healthcare services, and realizing the continuous improvement of all processes. In both tangible and responsive, the gap was greater than the other dimensions. It is recommended that more attention should be paid to the physical appearance of the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Vafaee-Najar et al (16) showed, in their study, that empathy had the lowest gap, which was similar to our results. However, Zarei et al (1) and Bahadori et al (8) reported that empathy had the highest gap when compared to all of the other dimensions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Vafaee-Najar et al (16) showed, in their study, that empathy had the lowest gap, which was similar to our results. However, Zarei et al (1) and Bahadori et al (8) reported that empathy had the highest gap when compared to all of the other dimensions.…”
Section: Discussionsupporting
confidence: 93%
“…The highest gaps in this study were in the tangibles (-0.33) and reliability (-0.30), and Vafaee-Najar et al (16) showed similar results. However, Aghamolaei et al showed that the gaps in the responsibility and empathy were higher than in the other dimensions (2).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Today, the PHC in Iran has many achievements and various successes in promoting health indexes (18). Despite these achievements, the country is facing emerging challenges related to demographic transition including population aging, changes in people needs, the unsustainability of resources, and hospital-centered health services (19,20). Therefore, these factors bring about an urgent need to accentuate elderly health needs in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The most important of these challenges are the changing of disease patterns from infectious to chronic, the population aging, unsustainability of resources, hospital-centered health services, use of untrained physicians in managerial positions, deterioration of health centers' building, changes in people's needs, increasing urbanization and growing marginal areas of cities with special health needs. 7,8 Therefore, the need for fundamental reforms in the management and provision of PHC, especially in urban areas, seems unavoidable. 9 Today, different strategies have been used to cope with the challenges of health care system in different countries.…”
Section: Introductionmentioning
confidence: 99%